Women in Security Changing the Face of Technology and Innovation (Women in Engineering and Science,, 2018)
This volume examines core areas of development in security, emphasizing the pivotal contributions of women to the field's evolution. The author first covers a broad spectrum of key topics, including how security is created, where innovation occurs, what the underpinnings are, and who supports it and how. After an overview of the field, female security professionals share their own stories of technology and innovation in security today; the foundation, where research is headed, and the emerging trends. Women currently make up a very small pocket of cyber security staffing - this book aims to increase the visibility of women in the field and their contributions and encourage other females to join the field. The contributors hold various roles from executive leadership, to engineers, analysts, and researchers. Identifies technology and innovation achievements from women in security Demonstrates the diverse segments, opportunities, and talents that make up the field of security Presents developments and advancements in cybersecurity and showcases women who are leading the way.